2005
DOI: 10.1111/j.1471-0528.2005.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery and severe stress incontinence. A cross‐sectional study among 2625 perimenopausal women

Abstract: Objective To estimate the prevalence of severe stress urinary incontinence (SUI) among perimenopausal women and to examine potential obstetric risk factors. Design Mail survey of female volunteers for epidemiological research.Setting Postal questionnaire on SUI.Population Three thousand one hundred and fourteen women aged 49 -61 years who comprised the GAZEL cohort. Methods Logistic regression using data from the entire cohort to estimate the impact of risk factors. A second logistic regression using data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
2
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 26 publications
1
41
2
13
Order By: Relevance
“…20 A study that included 182 Jordanian women between 50 and 65 years showed that body mass index (BMI) had no significant correlation with SUI. 21 Fritel et al analyzed questionnaires answered by 2,625 women between 49 and 61 years and found increased prevalence of SUI associated with parity, but did not find a correlation with vaginal delivery, 22 and this finding does not agree the finding by other authors describing vaginal delivery as a leading cause of neuromuscular impairment of pelvic floor and UI. 23 Donforth et al found an association between type 2 diabetes mellitus and smoking with UI.…”
Section: Introductioncontrasting
confidence: 52%
“…20 A study that included 182 Jordanian women between 50 and 65 years showed that body mass index (BMI) had no significant correlation with SUI. 21 Fritel et al analyzed questionnaires answered by 2,625 women between 49 and 61 years and found increased prevalence of SUI associated with parity, but did not find a correlation with vaginal delivery, 22 and this finding does not agree the finding by other authors describing vaginal delivery as a leading cause of neuromuscular impairment of pelvic floor and UI. 23 Donforth et al found an association between type 2 diabetes mellitus and smoking with UI.…”
Section: Introductioncontrasting
confidence: 52%
“…29 A history of gynaecological surgery for prolapse increased the risk of developing stress leakage over twofold, and hysterectomy and other gynaecological procedures also doubled the risk. 30,31 …”
Section: Other Risk Factorsmentioning
confidence: 99%
“…This work made it possible to show that urinary incontinence and pelvic organ prolapse have a significant impact on women's quality of life, such that one can talk of a urinary or pelvic handicap (Saadoun et al, 2006;Fritel et al, 2009). Contrary to generally accepted ideas, stress urinary incontinence, anal incontinence, and prolapse symptoms do not appear to be associated with women's obstetric history or hormonal status (Fritel et al, 2005(Fritel et al, , 2007. …”
mentioning
confidence: 53%